The Effect Of Work Ability And Organizational Culture On The Performance Of Officers With Motivation As A Mediator In Employment And Development Human Resources (Bkpsdm) Of Cilegon City - Ningtyas, Dian Novia; Mukhlis, Ahmad; Suadma, Udin (Fakultas Ekonomi & Bisnis Universitas Muslim Indonesia, 2025)
Employee performance is one of the key factors determining organizational success. Improving performance is not only dependent on technical skills but is also influenced by internal factors such as organizational culture and work motivation. A strong organizational culture can shape employees’ behavior, attitudes, and work ethic, while work motivation serves as a driving force in achieving predetermined targets. In this context, work ability becomes an essential element that bridges the influence of organizational culture and work motivation on employee performance. This study aims to analyze the effect of organizational culture and work motivation on employee performance, both directly and through work ability as a mediating variable. Through this approach, the research seeks to provide a comprehensive understanding of the role of work ability in enhancing employee performance within government institutions. The study employed a quantitative approach with data collected through questionnaires distributed to employees in the relevant institution. The sample size was determined using a purposive sampling method. Data analysis was conducted using Structural Equation Modeling (SEM) based on Partial Least Square (PLS) to examine the relationships between variables and identify the mediating role of work ability. The results indicate that organizational culture has a positive and significant effect on both work ability and employee performance. Work motivation also has a positive and significant effect on work ability and employee performance. Furthermore, work ability was found to mediate the effect of organizational culture and work motivation on employee performance. These findings reinforce the view that an optimal organizational culture and high work motivation can enhance work ability, ultimately leading to improved performance. The implications of this study highlight the need to strengthen organizational culture through clear work values, a fair reward system, and a conducive work environment. Additionally, management should enhance employee motivation by providing opportunities for self-development, continuous training, and recognition of work achievements. Future research is recommended to include moderating variables such as leadership style or work climate to provide broader insights into the determinants of employee performance.